E-barter vs. Fiat money: will central banks survive? - Capie, F; Wood, G (University of Oxford, 2003)
New technology in computing has led some to suggest that the ability to settle transactions electronically will develop to such an extent that money disappears from use. Two versions of this belief exist. One maintains that there will be â€